EDP – Portugal's main energy producer that everyone loved to hate. Issue 6 (30th March 2019) - Silva, Joao Carlos Marques; Azevedo Pereira, José
Abstract : Research methodology: This study has used public sources, interview with one of the case protagonists. Case overview/synopsis: This business case portrays the problems that an energy producing company faced in Portugal, in its transition from being a public company to becoming privatized. The Portuguese Government issued EDP with generous subsidies to guarantee its future profits and privatization success, but a few years later, after EDP was fully privatized, there was great political pressure to downsize such subsidies. The case describes the main steps taken by EDP from its creation and privatization, culminating at the end of 2017, where it was heavily criticized by media and political parties due to a high value of subsidies that had been granted to the company by the Portuguese Government in the past, while it was still a public company, and the renegotiation of those same subsidies after it had been privatized. EDP's President António Mexia was under police investigation due to having led the renegotiation talks in 2007, and it was feared that EDP's investors could refrain from investing in the company. Should EDP campaign to clear its good name, or would it be better to let the matter fall with the passing of time? Could the share value be affected? Should EDP prepare itself for loss of revenue due to an eventual downsizing of the subsidies? Complexity academic level: This study covers energy sector, privatization issues and government support. The relevance of this study is good for use in Business Schools and MBA courses.